Capacity, equity, empowerment and sustainability Focusing on Gawad Kalinga's Gawad Kabuhayan at Brgy. Naparaan, Salcedo, Eastern Samar. - Odivilas, Thea Amor O. (Tacloban City Thea Amor O. Odivilas, 2009)
This study intended to find out the capacity, equity, empowerment and sustainability: Focusing in Gawad Kalinga's Gawad Kabuhayan at Brgy. Naparaan, Salcedo, Eastern Samar. This study proved to be useful in evaluating how involved and empowered the GK residents are. This assessed how effective Gawad Kanuhayan is as a tool for empowerment, development, and democratization.
Development and democratization are two inseparable entities. With democratization, development will surely follow. With the citizens' cooperation and participation in the political process to promote policies and programs that help democratization, development will soon follow.
Gawad Kabuhayan in GK-ANCOP Australian Village plays an important role in giving the people the capacity to improve their income. Gawad Kalinga residents, through Gawad Kabuhayan, are equipped with knowledge, education, skills and materials. Aside from giving them new and decent houses, they are also given a chance to live a new life, free from hunger. This is just an example of a successful undertaking of an NGO.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science